Effect of Galvanic Corrosion on the Degradability of Biomedical Magnesium - Peng, Hongzhou; Wang, Wei; Jiang, Haomiao; Zan, Rui; Sun, Yu; Yu, Song; Ni, Jiahua; Wang, Wenhui; Wang, Tao; Wang, Jian; Zhang, Xiaonong (Frontiers in Materials, 2021)
With recent progress in clinical trials and scale-up applications of biodegradable magnesium-based implants, the scenarios of transplanting biodegradable Mg with other non-degradable metals may occur inevitably. Galvanic corrosion appears between two metallic implants with different electrochemical potentials and leads to accelerated degradation. However, a quantitative measurement on the galvanic corrosion of Mg in contact with other metallic implants has not been conducted. Here we study the corrosion behaviors and mechanical attenuation of high purity magnesium (Mg)in contact with stainless steel (316L), pure titanium (TA2), and magnesium alloy (AZ91) respectively to form different galvanic couples in simulated body fluids. The results show that all of these three heterogeneous metal pairs accelerate the degradation of high purity Mg to different degrees, yielding declined tensile strength and mechanical failure after 4 days of immersion. Our observations alert the potential risk of co-implanting different metallic devices in clinical trials.